2008
DOI: 10.1159/000119696
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Emergencies in Cardiac Surgery

Abstract: Objectives: The aim of this study is to retrospectively analyze risk factors, diagnosis and management of gastrointestinal (GI) complications following cardiac operations. Methods: Patients who developed GI complications after a cardiac operation were studied. Anesthesia protocols, techniques of cardiac surgery, potential risk factors, complications and medical and surgical interventions were reviewed and analyzed. Results: Out of 3,724 consecutive patients undergoing heart operations during an 8-year period, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Acute renal failure, new-onset AF, myocardial infarction, stroke, and sepsis were statistically significantly more frequent in patients with GICs in the postoperative period. The length of hospital stay of patients with GIC was statistically significantly longer than that of Age (year) [2,5,8,9,[12][13][14][15][16][17]19,21,22,24,25] 4.88 Female [2][3][4][5][6][7][8][9][11][12][13][14][15][16][17][18][19][20][21][23][24][25] 0.91 Hypertension [3,5,[7][8][9]11,12,[14][15][16][18][19]…”
Section: No Gi Complicationsmentioning
confidence: 99%
“…Acute renal failure, new-onset AF, myocardial infarction, stroke, and sepsis were statistically significantly more frequent in patients with GICs in the postoperative period. The length of hospital stay of patients with GIC was statistically significantly longer than that of Age (year) [2,5,8,9,[12][13][14][15][16][17]19,21,22,24,25] 4.88 Female [2][3][4][5][6][7][8][9][11][12][13][14][15][16][17][18][19][20][21][23][24][25] 0.91 Hypertension [3,5,[7][8][9]11,12,[14][15][16][18][19]…”
Section: No Gi Complicationsmentioning
confidence: 99%
“…[15] In a retrospective analysis that was published in 2008 that analyzed risk factors of gastrointestinal complications after cardiac surgeries, found that the decrease in blood flow and thus DO2 results in a state that the GI tract is not capable to recompense, because it doesn't have the ability of autoregulation. [16] Furthermore this state of hypoperfusion might be continued even after the re-establishment of adequate flows and pressures. A study that compared the importance of flow versus pressure during CPB in rabbits using laser Doppler flowmetry showed that the low splanchnic perfusion during CPB in mainly reliant on the pump blood flow.…”
Section: Blood Flow During Cpb: Goals and Requirementsmentioning
confidence: 99%
“…However, most of the other studies described gastrointestinal complications after cardiac surgery in general. Others compared colectomy of all causes to patients who were treated medically without surgical intervention [8, 9]. A comparison of medically treated patients with colonic complications after cardiac surgery is not eligible in our view.…”
Section: Commentmentioning
confidence: 99%